2013
DOI: 10.1016/j.freeradbiomed.2012.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Active secretion and protective effect of salivary nitrate against stress in human volunteers and rats

Abstract: Up to 25% of the circulating nitrate in blood is actively taken up, concentrated, and secreted into saliva by the salivary glands. Salivary nitrate can be reduced to nitrite by the commensal bacteria in the oral cavity or stomach and then further converted to nitric oxide (NO) in vivo, which may play a role in gastric protection. However, whether salivary nitrate is actively secreted in human beings has not yet been determined. This study was designed to determine whether salivary nitrate is actively secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…For instance, nitrite and nitrate are important protective elements of the oral and mucosal immune response, especially in settings of stress and periodontal injury[86,193,231]. Nitrite can exert pH-dependent antimicrobial effects[204,232,233] via formation of reactive secondary nitrogen oxides that can disrupt aerobic respiration[234], inhibit bacterial acid production, and disrupt biofilm formation[235237].…”
Section: The Oral Microbiome and Bacterial Nitrate Reductionmentioning
confidence: 99%
“…For instance, nitrite and nitrate are important protective elements of the oral and mucosal immune response, especially in settings of stress and periodontal injury[86,193,231]. Nitrite can exert pH-dependent antimicrobial effects[204,232,233] via formation of reactive secondary nitrogen oxides that can disrupt aerobic respiration[234], inhibit bacterial acid production, and disrupt biofilm formation[235237].…”
Section: The Oral Microbiome and Bacterial Nitrate Reductionmentioning
confidence: 99%
“…Oxidative stress is defined as the overproduction of free radicals, such as reactive oxygen species and reactive nitrogen species accompanied by the inability of endogenous defensive antioxidant enzymes to detoxify these free radicals (11). Nitrates, a nitric oxide (NO) metabolite present in different tissues and the chief reactive nitrogen species constituent, is a marker of oxidative stress and is implicated in associated disorders (13); NO increases in acute anxiety (14,15). Furthermore, various animal studies have reported higher NOx in the hippocampus and brain cortex of a stressed animal (16).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that long-term supplementation of drinking water with dietary nitrate reduced stress-induced gastric damage in the bilateral parotid and submandibular gland duct ligature in rats (BPSDL) (Jin 2013). That ligature completely blocked nitrate secretion by the salivary glands, resulting in decreased gastric nitrate (60 %), nitrite (66 %), and NO (62 %) concentrations.…”
Section: Discussionmentioning
confidence: 99%